Frequency hopping digital receiver and its implementation - Ge, Zaokun. (2008)
The emphasis of this thesis is on the design and implementation issues of a frequency hopping (FH) spread-spectrum (SS) system. In particular, a fast Fourier transform (FFT) based FH digital receiver was explored. Simulation results showed that the FFT-based receiver gave comparable performance with respect to the con-ventional match-filter receiver under partial-band noise jamming (PBNJ).